Analisis patentability alat sunat sekali pakai pada pengembangan desain industri A00202202524 - Achmad Fauzan Hery Soegiharto; Mohammad Isrok (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2023)
Industrial Design A00202202524, is about a circumcision device, which is called a modern circumcision device or a disposable circumcision device. The tool was designed taking into account the creator's experience, prior art, functional review and the anatomy in which the tool is used. Design development has been obtained and the product has been tested with good success. As a follow-up, we want to know the patent ability of the new design. The method used is a search of the closest related patents as a comparison document, both Indonesian and international. Analysis of similarities and differences between the invention product and the comparison document or prior art. From the patents found, 5 Indonesian patents and 8 international patents were selected. Indonesia. The conclusions obtained are: the product/invention is different from the comparison documents. Certain features of findings or creations or inventions are the answer to a technical problem, which has an invention step, and is new. Such creations or inventions have the potential to obtain a patent if the draft patent is properly formulated